On the didactic function on the artist monograph - Vincenzo Paudice (Intrecci d'arte, 2017)
In recent decades the debate on the "role" and "future" of the monograph in art and humanities research has flared up again in Europe, especially in France and England. Even though there are not homogenous positions, this debate shows how important it still is for the arts and humanities field to have a monograph approach. Particularly in history of art, this method is regarded as an "outil indispensable” - as Pierre Rosenberg writes in his introduction to the conference proceedings on Monographie d’artiste - in the academic path of the "future historien de l’art".The main focus of this paper is the artist monograph and how - mainly by virtue of both its tripartite structure and its “prosopopoeia” function - is the best methodological choice for students in their graduation thesis, in so far as it allows the greater acquisition of the necessary and specific knowledge and skills required in the field of the history of art.